Pengaruh Teknologi dan Inovasi terhadap Perekonomian Negara-Negara Muslim di Indonesia - Intan Ratnasari; Mohammad Daffa Dhiya Ulhaq; Mochammad Yuda Adipradana (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
.  Technological development and innovation play an important role in driving economic growth in various countries, including those with predominantly Muslim populations such as Indonesia. This study aims to analyze the influence of technological development on economic growth, examine the role of innovation in enhancing the competitiveness of the Islamic economy, and identify the opportunities and challenges of utilizing technology in the economic activities of Muslim communities in Indonesia. The research employs a qualitative approach through a literature review of various scholarly journal sources. The findings indicate that digital technology significantly contributes to increased productivity, economic efficiency, and expanded market access for businesses, particularly Micro, Small, and Medium Enterprises (MSMEs). In addition, innovations in the Islamic financial sector, such as Islamic fintech, have improved financial inclusion among the public. However, several challenges remain, including low levels of digital literacy, disparities in technological infrastructure, and the need for effective supervision to ensure that technological applications remain consistent with Islamic principles. Therefore, collaboration among the government, private sector, and society is essential to maximize the benefits of technology and innovation in achieving inclusive and sustainable economic development.